The Influence of Quality, Easy of Use, and Price on Product Attractiveness and Its Impact on Use Decisions (Study of Suroboyo Bus Service Users) - Achmad Rifky Kiemas; Nurul Azizah (Jurnal Ekonomi dan Bisnis Digital, 2023)
The increase in the number of motor vehicles is occurring in various cities in Indonesia, just like in Surabaya. This demands the Surabaya City government to reduce traffic congestion with several solutions, like increase the number of public transportation fleets. Suroboyo Bus, as one of the public transportation options in Surabaya, is required to meet the needs and desires of the Surabaya residents so that its user numbers will increase and contribute to reducing congestion. This research aims to determine the extent of the influence of quality, ease of use, price, product attractiveness, ease of use, and user decisions, both directly and indirectly, on Suroboyo Bus users in Surabaya. The method used in this research is the associative quantitative method. The respondents in this study were 100 respondents selected through purposive sampling. Data processing was carried out using path analysis method with the assistance of PLS software version 9.0.4.5.